Biology of the Gramineae Family and Development Periods of Cereal Crops - Ma’murakhan, Atabayeva; qizi, Xusanova Shahnoza Vohidjon (American Journal of Biology and Natural Sciences, 2024)
Growth and development are the processes that determine the productivity of grain crops. Growth is the increase of dry matter, development is the process of formation of plant organs, which fulfills its main biological function in preserving its species. Cereals include wheat, rice, maize, oats, barley, rye, millet, white sorghum, and sugarcane, among the important cultivated cereal crops.